2017
DOI: 10.3389/fpsyg.2017.01064
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement in Physics-Chemistry: The Predictive Effect of Attitudes and Reasoning Abilities

Abstract: Science education plays a critical role as political priority due to its fundamental importance in engaging students to pursue technological careers considered essential in modern societies, in order to face scientific development challenges. High-level achievement on science education and positive attitudes toward science constitutes a crucial challenge for formal education. Several studies indicate close relationships between students’ attitudes, cognitive abilities, and academic achievement. The main purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
5
28
0
1
Order By: Relevance
“…This finding is in agreement with that of Vagg, Bolger, Balta, & Lone (2020) that students like when multimedia are integrated in their school's curriculum. Likewise, this finding is in agreement with that of Vilia, et al (2017) carried out among some 9 th grade Portuguese students that both attitude and cognitive variables have impacts on the academic achievement of students in science education, and both should be considered when designing educational interventions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in agreement with that of Vagg, Bolger, Balta, & Lone (2020) that students like when multimedia are integrated in their school's curriculum. Likewise, this finding is in agreement with that of Vilia, et al (2017) carried out among some 9 th grade Portuguese students that both attitude and cognitive variables have impacts on the academic achievement of students in science education, and both should be considered when designing educational interventions.…”
Section: Discussionsupporting
confidence: 90%
“…Utilizing such packages made the learning of Biology very interesting. This finding is similar to that of Vilia, et al (2017) that revealed that attitude has a significantly positive relationship with students' achievement. This has implications for teaching and learning in schools.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, even though the prediction of academic performance has been widely explored and well-established in relation to cognitive factors such as intelligence or basic cognitive processes, there is a broad consensus that multiple cognitive, personality and motivational variables contribute in an interrelated form to predict individual differences in academic achievement (see, e.g., Ackerman and Heggestad, 1997 ; Chamorro-Premuzic and Furnham, 2008 ). For instance, personality predicts academic performance, even when intelligence and cognitive factors are controlled in adolescents (Noftle and Robins, 2007 ; Leeson et al, 2008 ); academic motivation (Lee and Shute, 2010 ), attitudes (Vilia et al, 2017 ), approaches to learning, prior knowledge, study time, homework parents ′education level are also associated to academic achievement (Núñez et al, 2014 ). Therefore, student related factors, school environment and peer influences not studied here should also be included to better assess students learning in future research.…”
Section: Discussionmentioning
confidence: 99%
“…In our modern technologically advanced society, it is essential to be scientifically literate, and it has become increasingly important for society that there are individuals willing and able to pursue careers within the science and technology field (Tytler, 2014; Vilia et al, 2017). Despite the importance of acquiring and possessing adequate skills and knowledge in science, few studies have explored the mechanisms underlying children’s basic skills in science.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant research shows that logical reasoning is one key component underlying skills in science (e.g., van der Graaf et al, 2015; Vilia et al, 2017; Berkowitz and Stern, 2018). The reason for this dependence upon logical reasoning is rather straightforward as acquiring skills in science involves learning about abstract scientific facts, theories, and applying complex scientific methods (Klahr et al, 2011; Kuhn, 2011).…”
Section: Introductionmentioning
confidence: 99%